Internationalisation and the global South - Sergio Celis; Carolina Guzmán-Valenzuela (University of Johannesburg, 2021)
This special issue of SOTL in the South tackles the internationalisation of the scholarship of teaching and learning in the global South. In examining internationalisation as a means of driving globalisation, there is a group of forces that work together in a complex intersection that involve financial, military, environmental, migratory, technological, cultural, and political dimensions (Giddens, 1990). Many of these global forces are driven by commercial aims and flow from post-capitalism. In this context, this special issue portrays the struggles of conceiving and enacting internationalisation on campuses in the global South. These struggles are increasingly part of universities, yet this special issue also shows how Southern responses to internationalisation emerge from these struggles and project new practices inspired by the idea of intercultural education.